New submerged arc welding flux for hardfacing of Hardox steels - Kaptanoglu, Mustafa; Odabasi, Akin (Carl Hanser Verlag, 2020)
In this study, the usability of a new submerged arc welding flux was investigated to develop the surface properties of Hardox steels. In the hardfacing welding processes for Hardox 400 steel, four welding speeds resulting in varied heat inputs were applied. Through an analysis of the chemical composition, microstructure examinations, hardness measurements and wear tests, the possibility of hardfacing properties control due to the change of process parameters were determined. In the experimental studies, the hardness of the hardfacing obtained at a welding speed of 30 cm x min(-1) was measured as 42 HRC while the hardness of the hardfacing obtained at a welding speed of 48 cm x min(-1) was measured as 57 HRC. Moreover, in the wear tests, results consistent with the hardness values were obtained. It was understood in the light of the results that the use of high carbon ferro-chromium 20 wt.-% in a submerged arc welding flux mixture may be useful in improving hardness and wear properties of Hardox steels through hardfacing welding processes.
Keywords: Hardox steel; submerged arc welding; hardfacing; welding speed; ferro-chromium